2019
DOI: 10.1158/1541-7786.mcr-18-1109
|View full text |Cite
|
Sign up to set email alerts
|

HIF Inactivation of p53 in Ovarian Cancer Can Be Reversed by Topotecan, Restoring Cisplatin and Paclitaxel Sensitivity

Abstract: Ovarian cancer growth under hypoxic conditions results in hypoxia-inducible factor-1a (HIF1a) stabilization. HIF1a is an adverse prognostic factor that may contribute to worse outcomes via its capacity to bind to p53, potentially blocking p53-mediated apoptosis. We determined whether HIF1a-p53 binding occurred in hypoxic ovarian cancer cell lines, and if this blocked p53 transcriptional activity. Topotecan (TPT), used in the treatment of ovarian cancer, inhibits HIF1a translation via a topoisomerase-1 (TOPO1)-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 42 publications
0
22
0
1
Order By: Relevance
“…Moreover, siRNA inhibition of HIF1-α also decreased MDR1 and restored PTX sensitivity [291]. MDR1 expression was increased in hypoxic conditions but was reduced following treatment with the clinical topoisomerase 1 inhibitor topotecan (TPT) [292], further supporting the interaction between HIF1-α levels and drug efflux pumps in taxane resistance. TPT indirectly inhibits HIF1-α by preventing its translation [292,293].…”
Section: Hypoxia Response Pathwaymentioning
confidence: 88%
See 2 more Smart Citations
“…Moreover, siRNA inhibition of HIF1-α also decreased MDR1 and restored PTX sensitivity [291]. MDR1 expression was increased in hypoxic conditions but was reduced following treatment with the clinical topoisomerase 1 inhibitor topotecan (TPT) [292], further supporting the interaction between HIF1-α levels and drug efflux pumps in taxane resistance. TPT indirectly inhibits HIF1-α by preventing its translation [292,293].…”
Section: Hypoxia Response Pathwaymentioning
confidence: 88%
“…MDR1 expression was increased in hypoxic conditions but was reduced following treatment with the clinical topoisomerase 1 inhibitor topotecan (TPT) [292], further supporting the interaction between HIF1-α levels and drug efflux pumps in taxane resistance. TPT indirectly inhibits HIF1-α by preventing its translation [292,293]. Though successful at inhibiting HIF1-α, TPT is not effective enough as a monotherapy and may only benefit patients with increased hypoxia signal and the presence of topoisomerase 1.…”
Section: Hypoxia Response Pathwaymentioning
confidence: 93%
See 1 more Smart Citation
“…Reduction of topoisomerase I protein expression was observed in NCI-H460 cells treated with 30 nM TPT and the combination of TPT and 5 µM CBZ, as well as in NCI-H460/TPT10 cells treated with the drug combination. It has been reported that TPT could decrease the protein expression of topoisomerase I in ovarian cancer cells and breast cancer cells (D'Onofrio et al, 2011;Parmakhtiar et al, 2019). The downregulation of topoisomerase I expression in NCI-H460 cells upon TPT or combination treatment and in NCI-H460/TPT10 cells upon combination treatment may be explained by the accumulated TPT in NCI-H460 cells and the restored TPT level by CBZ in NCI-H460/TPT10 cells.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that inhibition of P53 transcriptional activity is associated with paclitaxel resistance in ovarian cancer cells, and restore P53 transcriptional activity can reverse paclitaxel sensitivity. 47 Hailing Yang et al reported that P53 expression was upregulated in ovarian cancer cells after paclitaxel stimulation, and the overexpression of TAP63, a P53 family member, led to apoptosis in paclitaxel-resistant ovarian cancer cells after treatment with paclitaxel. 48 According to these studies, we speculate that Fos is a potential target for the regulation of paclitaxel sensitivity, and maybe participates in the regulation via suppressing P53's apoptotic contribution to drug response in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%